Do Institutional and Psychological Supports Foster Islamic Entrepreneurial Intention? Evidence from Productive Zakat Beneficiary Students in Indonesia and Malaysia - Ahmad Ajib Ridlwan; Yan Putra Timur; Fitriah Dwi Susilowati; Muhamad Nafik Hadi Ryandono; Juliana Juliana; Shafinar Ismail (Universitas Muhammadiyah Surakarta, 2026)
This study examines the determinants of Islamic entrepreneurial intention among productive zakat scholarship recipients in Indonesia and Malaysia. Data from 142 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the effects of university support, perceived organizational support, and self-efficacy. The results show that university support and perceived organizational support significantly enhance self-efficacy, indicating the importance of institutional support in strengthening entrepreneurial confidence. University support also positively influences Islamic entrepreneurial intention, while perceived organizational support does not have a direct effect on intention. Self-efficacy emerges as the strongest predictor of Islamic entrepreneurial intention, highlighting its central role in translating institutional support into entrepreneurial motivation. The multi-group analysis reveals differences between Indonesia and Malaysia: in Indonesia, perceived organizational support strongly strengthens self-efficacy, which subsequently drives entrepreneurial intention, whereas in Malaysia, university support improves self-efficacy but does not significantly translate into intention. These findings suggest that the impact of institutional support on Islamic entrepreneurial intention is context-dependent across countries. Universities and zakat institutions should complement financial assistance with mentoring, business incubation, and networking opportunities to strengthen entrepreneurial intention among scholarship recipients. The study contributes to the literature by providing comparative evidence from Indonesia and Malaysia on the role of institutional support in shaping Islamic entrepreneurial intention.